1981
DOI: 10.1038/bjc.1981.172
|View full text |Cite
|
Sign up to set email alerts
|

Enhancing effect of misonidazole on the response of the RIF-1 tumour to cyclophosphamide

Abstract: Summary.-The effect of misonidazole (MISO) on the cytotoxicity of cyclophosphamide (CY) was investigated in the mouse.The response of the RIF-1 tumour was measured by growth delay and by cell survival in a cloning assay. MISO enhanced the cytotoxicity of CY. For single treatment, enhancement was maximal when MISO was given 30 min to 2 h before CY. The enhancement ratio (i.e. the dose of CY alone divided by the dose of CY with MISO required to cause the same response) increased with increasing dose of MISO up t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
28
2

Year Published

1982
1982
1992
1992

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(34 citation statements)
references
References 23 publications
(23 reference statements)
4
28
2
Order By: Relevance
“…The bulk of the data suggest that dose modification by a factor > 1.2 is unlikely. This is clearly less than the dosemodifying factors which have been seen following large single dose MISO in the RIF-1 tumour with CTX (Twentyman, 1981;Law et al, 1981) or in the KHT tumour with CCNU (Siemann, 1981;Workman and Twentyman, 1982). The results are contrary to those recently reported by Brown & Hirst (1982) who used a similar 7-h MISO protocol in the RIF-1 tumour and demonstrated clear sensitization to MEL and to CTX.…”
Section: Discussioncontrasting
confidence: 57%
See 1 more Smart Citation
“…The bulk of the data suggest that dose modification by a factor > 1.2 is unlikely. This is clearly less than the dosemodifying factors which have been seen following large single dose MISO in the RIF-1 tumour with CTX (Twentyman, 1981;Law et al, 1981) or in the KHT tumour with CCNU (Siemann, 1981;Workman and Twentyman, 1982). The results are contrary to those recently reported by Brown & Hirst (1982) who used a similar 7-h MISO protocol in the RIF-1 tumour and demonstrated clear sensitization to MEL and to CTX.…”
Section: Discussioncontrasting
confidence: 57%
“…At the same time, a number of in vivo studies (Rose et al, 1980, Clement et al, 1980Tannock, 1980;Law et al, 1981;Twentyman, 1981;Martin et al, 1981;Siemann, 1981) have found that administration of MISO to mice at or around the time of cytotoxic drug administration can increase the anti-tumour effect of the cytotoxic drug.…”
mentioning
confidence: 99%
“…The enhancement of tumour response may be a manifestation of the pre-incubation effects seen in vitro, though alternative mechanisms have been suggested (Law et al, 1981;Workman & Twentyman, 1982). In most instances MISO/cytotoxic-drug combinations show greater effects on tumours than on some normal tissues.…”
Section: Methodsmentioning
confidence: 99%
“…It is known that MISO enhances antitumour activity of various alkylating agents in vivo (Rose et al, 1980;Clement et al, 1980;Tannock, 1980a,b;Law et al, 1981;Martin et al, 1981;Siemann, 1981;Mulcahy et al, 1981;Stephens et al, 1981;Twentyman, 1981). Enhancement of the cytotoxic action of melphalan also occurs in vitro (Stratford et al, 1980;Roizin-Towle & Hall, 1981).…”
mentioning
confidence: 99%
“…ther, pretreatment in vitro of hypoxic cells with misonidazole renders the cells more sensitive to the cytotoxic action of some chemotherapeutic agents (Stratford et al, 1980). Several in vivo studies have shown that MISO apparently potentiates the anti-tumour activity of some chemotherapeutic drugs, particularly alkylating agents, in a variety of experimental tumours (Clement et al, 1980;Rose et al, 1980;Tannock, 1980;Siemann, 1981;Mulcahy et al, 1981;Law et al, 1981;Martin et al, 1981;Twentyman, 1981 (Sheldon & Hill, 1977), by subsequent monolayer cloning (McNally & Sheldon, 1977) and by subsequent soft-agar cloning Clonogenic assay.-Tumour response was assayed by a modification of the soft-agar cloning technique described by Stephens et al (1980). Eighteen hours after treatment, individual tumours were excised, scraped free of muscle, minced with curved scissors, weighed, suspended in 10 ml PBS, 10 mg trypsin and 0 5 mg DNase added, and rotated at 120 rev/min for 20 min in a 37°C chamber.…”
mentioning
confidence: 99%